Discrimination of Ipomoea aquatica cultivars and bioactivity correlations using NMR-based metabolomics approach - Lawal, U.; Maulidiani, M.; Shaari, Khozirah; Ismail, Intan Safinar; Khatib, A.; Abas, Faridah (Taylor & Francis, 2017)
Ipomoea aquatica Forsk is a green leafy vegetable that is a rich source of minerals, proteins, vitamins, amino acids, and secondary metabolites. Different types of I. aquatica cultivars are grown for consumption but little is known about the metabolites variation. Proton nuclear magnetic resonance (1H NMR) spectroscopy combined with multivariate data analysis was applied for metabolic profiling of three I. aquatica cultivars including “broad leaf (K-25)”, “bamboo leaf (K-88)”, and “special pointed leaf (K-11)”. The orthogonal partial least squares discriminant analysis (OPLS-DA) indicated a clear separation among cultivars. The relative levels of various compounds, such as amino acids, organic acids, sugars, and phenolic compounds were specific to each cultivar. The K-11 cultivar was different from the other cultivars due to a high phenolic content. The content of sugars and some amino acids was higher in K-88 and K-25 possessed a higher content of organic acids. The in vitro study revealed that the I. aquatica cultivars exhibited potent antioxidant and α-glucosidase activities. The results of this study indicate that the K-11 cultivar was the most active due to the abundance of epicatechin, 4,5-dicaffeoylquinic, protocatechuic acid, and rutin.